PREGNANCY LEAVE'S IMPACT ON ENERGY BALANCE AND LABOR PERIOD IN WORKING MOTHERS - Inar Melati , Feras; Purwanto , Bambang; Umiastuti , Pirlina (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Maternity leave is a right of female workers granted by the government. Pregnant women have the right to rest for 1.5 months before giving birth and 1.5 months after giving birth according to Law No. 13 of 2003. Pregnant women who take late maternity leave are at risk of experiencing a longer second period. This study aims to determine the relationship between maternity leave and energy balance and the length of the second stage of labor. Method: The research method uses a comparative study approach because researchers will compare the energy balance and length of the second stage of labor in working mothers who take maternity leave and those who delay taking maternity leave. The sample in this study was mothers giving birth at RSI Jemursari Surabaya who met the inclusion criteria. The instruments used were medical record books, partograph sheets and data collection sheets. Research data was analyzed using Fisher's exact test. Result: The results showed that majority of respondents (77%) had a negative energy balance and majority of respondents (80.9%) experienced the second stage of labor in less than 90 minutes. The statistical test results of the maternity leave period with energy balance obtained a value of p = 1.000 and the results of statistical tests between the period of maternity leave and the second stage of labor obtained a value of p = 0.421. Conclusion: These data show that there is no relationship between the period of maternity leave and energy balance and there is no significant relationship between the period of maternity leave and the second stage of labor in working mothers.